The mystery of let-7d – a small RNA with great power - Kolenda, Tomasz; Przybyła, Weronika; Teresiak, Anna; Mackiewicz, Andrzej; M. Lamperska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2014)
miRNAs belong to a class of small non-coding RNAs which can modulate gene expression. Disturbances in their expression and function may cause cancer formation, progression and cell response to various types of stress. The let-7 family is one of the most studied groups of miRNAs. The family contains 13 members with similar sequences and a wide spectrum of target genes. In this paper, we mostly focus on one member of the family - let-7d. This miRNA is dysregulated in many types of cancers. It can be over- or down-expressed, and it acts as a tumor suppressor or oncogene. It regulates various genes such as LIN28, C-MYC, K-RAS, HMGA2 and IMP-1. Moreover, let-7d has a significant impact on epithelial-to-mesenchymal transition (EMT) and formation of cancer initiating cells which are resistant to irradiation and chemical exposure and responsible for cancer metastasis. Let-7d can serve as a prognostic and predictive marker for personalization of the treatment. Let-7d is a small RNA with great power, but in different cell genetic backgrounds it acts in different ways, which makes this molecule still mysterious.